A pirfenidone loaded spray dressing based on lyotropic liquid crystals for deep partial thickness burn treatment: healing promotion and scar prophylaxis. Issue 13 (9th March 2020) - Chen, Jintian; Wang, Hui; Mei, Liling; Wang, Bei; Huang, Ying; Quan, Guilan; Lu, Chao; Peng, Tingting; Pan, Xin; Wu, Chuanbin
Abstract : This study develops a HA combined lyotropic liquid crystal based spray dressing loaded with pirfenidone for wound healing and scar prophylaxis. Abstract : A deep partial thickness (DPT) burn injury refers to burn damage involving the epidermis and major dermis, whose prognosis depends greatly on wound management. Lack of effective management can lead to an elongated healing process and aggravated scar formation, which can severely disturb patients, both physically and mentally. A dressing with good water absorption and moderate mechanical properties is crucial for healing promotion, and the prevention of scar formation is highly desirable. In this project, a hyaluronic acid combined lyotropic liquid crystal based spray dressing (HLCSD) loaded with the anti-fibrotic drug pirfenidone (PFD) has been designed. HLCSD is expected to achieve the goals of both wound healing promotion and scar prophylaxis. Its water absorption capacity, mechanical properties, drug release behavior and phase transition are fully evaluated. HLCSD possesses low viscosity for spray administration and high levels of water absorption for exudate absorption. An in situ gel composed of self-assembled lattice nanostructures provides excellent mechanical protection to promote the healing process and steady PFD release to exert a scar prophylaxis effect. The benefit of HLCSD on the wound healing rate is verified in vivo . In the DPT burn wound model we established, HLCSD also exhibits excellent healing promotion effects, and PFD-loaded HLCSD shows scar prophylaxis effects and displays an ideal prognosis, with skin as smooth as healthy skin. The healing promotion of HLCSD is considered to be related to the alleviation of inflammation, with an obviously shortened inflammation phase, with contributions from water management, mechanical protection and anti-inflammation by HLCSD. The scar prophylaxis of PFD-loaded HLCSD is proven to be related to the regulation of collagen synthesis and degradation, involving key cytokines like TGF-β and MMP-1. Taken together, the PFD-loaded HLCSD with healing promotion and scar prophylaxis offers significant promise as a spray dressing for DPT burn injuries.